PENGARUH PEMBERIAN DOSIS PUPUK ORGANIK CAIR (POC) PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA (Lactuca sativa L.) DI GREEN HOUSE FMIPA UPG 1945 NTT - Adelina Tallo; Nur Aini Bunyani; Maya F. Roman; Deglory Tunmuni (CV. ADIBA AISHA AMIRA, 2026)
This study was conducted over a three-month period, from November 2025 to January 2026, at the FMIPA UPG 1945 NTT greenhouse in Oebobo District, Kupang City. The research aimed to determine the effect of applying Plant Growth-Promoting Rhizobacteria (PGPR) liquid organic fertilizer on the growth and yield of lettuce (*Lactuca sativa* L.) and to identify the most effective dosage. A Completely Randomized Design (CRD) was employed, featuring five treatments and six replications. The treatments consisted of P0 (control without PGPR), P1 (150 ml/liter of water), P2 (250 ml/liter of water), P3 (350 ml/liter of water), and P4 (450 ml/liter of water). Observed parameters included plant height, number of leaves, and fresh weight of the lettuce plants. Data were analyzed using Analysis of Variance (ANOVA), followed by the Least Significant Difference (LSD) test at the 5% level. The results indicated that the application of PGPR liquid organic fertilizer had a highly significant effect on lettuce growth and yield. The best results were obtained with a dosage of 450 ml/liter of water (P4), yielding an average plant height of 24.80 cm, 22.50 leaves, and a fresh weight of 134.67 grams. The enhanced plant growth is attributed to the ability of PGPR to increase nutrient availability, improve soil biological conditions, and produce growth hormones such as auxins, gibberellins, and cytokinins. Thus, the use of PGPR liquid organic fertilizer offers an environmentally friendly bio-fertilizer alternative for sustainably increasing lettuce productivity.